Blood levels of cobalt and chromium are inversely correlated to head size after metal-on-metal resurfacing arthroplasty. Issue 6 (November 2013) - Parry, Michael C.; Eastaugh-Waring, Steve; Bannister, Gordon C.; Learmonth, Ian D.; Case, Charles Patrick; Blom, Ashley W.
Resurfacing arthroplasty has fallen out of favour in recent years due to unfavourable survivorship in joint registries and alarming reports of soft tissue reactions around metal on metal prostheses. Our aim was to assess the effect of head size, implant design and component positioning on metal production by resurfacing arthroplasties. We measured whole blood cobalt and chromium and component position in matched populations implanted with two designs of resurfacing arthroplasty over a two-year period. Both implants resulted in a significant increase in blood metal levels (p<0.001) though the ASR design generated significantly higher metal levels (p = 0.041). A significant inverse correlation was seen between component size and blood cobalt levels (p = 0.032) and blood chromium levels (p<0.001). No correlation was identified between component position and blood metal levels. Small diameter metal resurfacing components result in increased metal generation compared with larger components. As increased metal generation has been correlated to wear and therefore failure, caution must be used on implantation of smaller components and indeed, in those who require smaller components, alternative bearing materials should be considered. These results contrast with recent findings which have demonstrated early failure for larger diameter stemmed metal-on-metal prostheses.